Side‐Gated In2O3 Nanowire Ferroelectric FETs for High‐Performance Nonvolatile Memory Applications. Issue 9 (15th April 2016) - Su, Meng; Yang, Zhenyu; Liao, Lei; Zou, Xuming; Ho, Johnny C.; Wang, Jingli; Wang, Jianlu; Hu, Weida; Xiao, Xiangheng; Jiang, Changzhong; Liu, Chuansheng; Guo, Tailiang
Abstract : A new type of ferroelectric FET based on the single nanowire is demonstrated. The design of the side‐gated architecture not only simplifies the manufacturing process but also avoids any postdeposition damage to the organic ferroelectric film. The devices exhibit excellent performances for nonvolatile memory applications, and the memory hysteresis can be effectively modulated by adjusting the side‐gate geometries.